2020
DOI: 10.21873/anticanres.14369
|View full text |Cite
|
Sign up to set email alerts
|

Papillary Thyroid Cancer Tumor Spheres Cultured by Passaging Without Sorting Exhibit Cancer Stemness

Abstract: Aim: Cancer stem-like cell (CSC) markers and the role of CSCs derived from papillary thyroid carcinoma (PTC) in pathogenesis are unclear. This study aimed to investigate CSC properties using tumor spheres from passaged PTC cells but without sorting CSCs. Materials and Methods: To identify the properties of CSCs derived from PTC, the expression of SRY-box transcription factor 2(SOX2), octamer-binding transcription factor 4 (OCT4), Nanog homeobox (NANOG), thyroglobulin (TG), thyroid-stimulating hormone receptor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Yes-associated protein (YAP1) is a direct effector in the downstream Hippo pathway, which regulates numerous protein targets for regulating gene level, cell contact, proliferation, or apoptosis [ 32 ]. Recent evidence indicated that PTC tumor spheres transfected with siRNA targeting YAP1 had less differentiation potential [ 33 ]. However, whether CENPK–YAP1–EMT axis is involved in the tumorigenesis of DTC needs further exploration.…”
Section: Discussionmentioning
confidence: 99%
“…Yes-associated protein (YAP1) is a direct effector in the downstream Hippo pathway, which regulates numerous protein targets for regulating gene level, cell contact, proliferation, or apoptosis [ 32 ]. Recent evidence indicated that PTC tumor spheres transfected with siRNA targeting YAP1 had less differentiation potential [ 33 ]. However, whether CENPK–YAP1–EMT axis is involved in the tumorigenesis of DTC needs further exploration.…”
Section: Discussionmentioning
confidence: 99%
“…polarized epithelial cuboidal thyroid follicular cells) to a fibroblastoid morphology that enables invasive capacity [21,22]. Cancer stem cells (CSC's) are a slowly dividing, relatively treatment-resistant population of cells that exhibit plasticity in response to therapeutic or environmental challenges and express genes and surface markers [21,[23][24][25]. Cells that have undergone EMT and CSCs are critical in all components of the metastatic cascade and demonstrate the considerable "plasticity" of cancer cells.…”
Section: Metastatic Spreadmentioning
confidence: 99%